2017
DOI: 10.1016/j.ecss.2017.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Field estimates of floc dynamics and settling velocities in a tidal creek with significant along-channel gradients in velocity and SPM

Abstract: A short-term intensive measurement campaign focused on flow, turbulence, suspended particle concentration, floc dynamics and settling velocities were carried out in a brackish intertidal creek draining into the main channel of the Scheldt estuary. We compare in situ estimates of settling velocities between a laser diffraction (LISST) and an acoustic Doppler technique (ADV) at 20 and 40 cm above bottom (cmab). The temporal variation in settling velocity estimated were compared over one tidal cycle, with a maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…A value of kA=0.5 and kB=5.0E‐6 worked reasonably well for the Markussen and Andersen () data (Figure a). These same values for kA and kB also produced comparable, yet poorer, results between the observations and predictions for the Schwarz et al () case (Figure b); however, no pairing of data kA and kB values was found to do much better. This is perhaps due in part to fact that the measured floc sizes are inversely related to G over most of the time series but then decreases with G over the tail end of the time series.…”
Section: Model Validationsupporting
confidence: 51%
See 4 more Smart Citations
“…A value of kA=0.5 and kB=5.0E‐6 worked reasonably well for the Markussen and Andersen () data (Figure a). These same values for kA and kB also produced comparable, yet poorer, results between the observations and predictions for the Schwarz et al () case (Figure b); however, no pairing of data kA and kB values was found to do much better. This is perhaps due in part to fact that the measured floc sizes are inversely related to G over most of the time series but then decreases with G over the tail end of the time series.…”
Section: Model Validationsupporting
confidence: 51%
“…All times in the studies have been shifted to start at time equals 0 hr to better reflect the different time scales involved in each study. For (a) Markussen and Andersen () and (b) Schwarz et al (), the measured velocity ranged from −0.7 to 0.8 and ≈0 to 0.4 m/s, respectively, during the time window displayed.…”
Section: Model Validationmentioning
confidence: 97%
See 3 more Smart Citations